2017
DOI: 10.1055/s-0043-102945
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Cycling Power Meters against a Mathematical Model of Treadmill Cycling

Abstract: The aim of this study was to compare the accuracy among a high number of current mobile cycling power meters used by elite and recreational cyclists against a first principle-based mathematical model of treadmill cycling. 54 power meters from 9 manufacturers used by 32 cyclists were calibrated. While the cyclist coasted downhill on a motorised treadmill, a back-pulling system was adjusted to counter the downhill force. The system was then loaded 3 times with 4 different masses while the cyclist pedalled to kee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 27 publications
1
50
2
Order By: Relevance
“…The accuracy of the power meter used in the current study may be questioned with regards to the observed differences. If the true power outputs are difficult to define accurately, a recent study underlined the decent precision (with a coefficient of variation of 2%) for the power meter utilized in the current study (Maier et al, 2017). This indicates a rather low day-today variability and allows to consider the observed differences in terms of power output with confidence.…”
Section: Limitationsmentioning
confidence: 62%
“…The accuracy of the power meter used in the current study may be questioned with regards to the observed differences. If the true power outputs are difficult to define accurately, a recent study underlined the decent precision (with a coefficient of variation of 2%) for the power meter utilized in the current study (Maier et al, 2017). This indicates a rather low day-today variability and allows to consider the observed differences in terms of power output with confidence.…”
Section: Limitationsmentioning
confidence: 62%
“…Trueness = -1.7 ± 1.1 vs. -0.5 ± 2.4%; Precision = 0.6 ± 0.4 vs. 0.8 ± 0.4%, respectively). 15 These small measurement errors might have resulted in the variability found in this study. Further, methodological variability in this study could have arisen from the environmental conditions and mathematical modelling.…”
Section: Discussionmentioning
confidence: 85%
“…The bicycle was equipped with a Verve Cycling InfoCrank power meter (Verve Cycling, Perth, Australia) containing four strain gauges per crank arm. 15 All tests were completed on a quiet, straight, and flat road. A high definition camera (Sony, Tokyo, Japan) was placed on the side of the road at the middle of the 250 m test section to film the participant's sagittal plane at 25 Hz.…”
Section: Experimental Designmentioning
confidence: 99%
“…Depending on the specific study protocol, the range of power outputs investigated and the brand/model, results vary with errors up to 16.5% (Gardner et al, 2004 ; Bertucci et al, 2005 ; Hurst and Atkins, 2006 ; Duc et al, 2007 ; Maier et al, 2017 ). While some individual devices have been shown to be inaccurate shortly after manufacturing (Gardner et al, 2004 ), other factors difficult to control, such as, ambient temperature, vibrations, and impacts from gear shifts, but also bicycle and power meter maintenance have been suggested as variables influencing the accuracy of power assessment (Gardner et al, 2004 ; Maier et al, 2017 ; Passfield et al, 2017 ). For the above mentioned reasons, the consistent accuracy of commercial power meter devices cannot not be presumed.…”
Section: Accuracy Of Power Metersmentioning
confidence: 99%
“…It is important to note that different calibration procedures may convey different results and as such the need for a standardization of calibration methodologies has been highlighted (Hawser, 2016 ). In this regard, the use of first principle-based calibration methods are recommended (Stein et al, 1967 ; Maier et al, 2017 ).…”
Section: Accuracy Of Power Metersmentioning
confidence: 99%